Review of Modernising school governance: Corporate planning and expert handling in state education - Emin Kilinc (Research in Social Sciences and Technology- OpenED Network, 2017)
Wilkins, A. (2016). Modernising school governance: Corporate planning and expert handling in state education. New York, NY: Routledge. 172 pp., ISBN-9781138787476. Modernising School Governance: Corporate Planning and Expert Handling in State Education is a part of Routledge Research in Education Policy and Politics series which aims to enhance readers understanding of key challenges and facilitate on-going academic debate within the influential and growing field of education policy and politics by Routledge. Andrew Wilkings, the author, is a senior lecturer in Education Studies at the University of East London. Modernising School Governance is a product of a three-year project conducted between 2012-2015 and supported by the Economic and Social Research Council (ESRC) in England.